Serum osteopontin levels as a predictor of portal inflammation in patients with nonalcoholic fatty liver disease - EREN, FATİH; ATUĞ, ÖZLEN; ÖZEN ALAHDAB, YEŞİM; YILMAZ, YUSUF (ELSEVIER SCIENCE INC, 2013)
Background: Osteopontin is a secreted phosphorylated glycoprotein that is expressed by a variety of cell types and that mediates numerous and diverse biological functions. Osteopontin knockout mice are protected from obesity-induced hepatic steatosis. In the present study, we sought to investigate whether serum osteopontin concentrations are associated with liver histology in patients with nonalcoholic fatty liver disease. Methods: Serum levels of osteopontin were measured by enzyme-linked immunosorbent assay in 179 Well-characterized patients with nonalcoholic fatty liver referred for liver histology and 123 control subjects. Results: Serum osteopontin levels were markedly higher in patients with nonalcoholic fatty liver disease than in controls (p < 0.001). Multivariable analysis showed that osteopontin levels were strongly and independently associated with both portal inflammation (beta = 0.294, p < 0.01) and serum aminotransferase levels (aspartate aminotransferase: beta = 0.295, p < 0.01; alanine aminotransferase; beta = 0.285, p < 0.01). Conclusion: In summary, these data demonstrate that serum levels of osteopontin are elevated in nonalcoholic fatty liver disease and are a significant independent predictor of portal inflammation in this clinical entity. (C) 2012 Editrice Gastroenterologica Italiana S.r.l. Published by Elsevier Ltd. All rights reserved.
Keywords: Biomarker; Inflammation; Nonalcoholic fatty liver disease; Osteopontin; Portal inflammation; METABOLIC SYNDROME; HEPATOCELLULAR-CARCINOMA; STEATOHEPATITIS; ASSOCIATION; STEATOSIS; OBESITY; MARKER; EXPRESSION; FIBROSIS; HEDGEHOG